2007
DOI: 10.1007/1-4020-5252-9_7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Response to Osmotic Shock

Abstract: Abstract:The cellular responses of cultured mammalian cells and non-mammalian organisms to changes in osmolarity are discussed. A number of common themes including activation of protein kinase cascades can be observed in a diverse group of organisms. A combination of physiological and transcriptional studies has been performed to identify regulatory factors and proteins that play a causal role in the cellular responses to osmotic changes. These factors may serve as targets for cellular engineering strategies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 102 publications
(119 reference statements)
0
3
1
Order By: Relevance
“…Evidence for this conclusion is that various compounds, such as glucose, sucrose, mannitol, or sorbitol, can reproduce the effect observed with NaCl. 4 , 20 , 27 , 30 Second, the yield increase described in our study was notably higher than the rate of increase reported for mAb production, with most studies reporting a relatively moderate mAb rate increase between 2- and 3-fold. 20 , 23 , 26 This is likely the result of critical differences between mAbs and rAAV production: mAb production relies essentially on transcription and translation in cells that are selected for this performance; on the contrary, rAAV production involves genome rescue and replication, gene expression, and genome packaging, all steps heavily controlled both by cellular and helper virus pathways.…”
Section: Discussioncontrasting
confidence: 70%
“…Evidence for this conclusion is that various compounds, such as glucose, sucrose, mannitol, or sorbitol, can reproduce the effect observed with NaCl. 4 , 20 , 27 , 30 Second, the yield increase described in our study was notably higher than the rate of increase reported for mAb production, with most studies reporting a relatively moderate mAb rate increase between 2- and 3-fold. 20 , 23 , 26 This is likely the result of critical differences between mAbs and rAAV production: mAb production relies essentially on transcription and translation in cells that are selected for this performance; on the contrary, rAAV production involves genome rescue and replication, gene expression, and genome packaging, all steps heavily controlled both by cellular and helper virus pathways.…”
Section: Discussioncontrasting
confidence: 70%
“…The hypo‐osmotic stress response of C. cryptica shared features of “general” environmental stress responses seen in other eukaryotes (Gasch et al, 2000; Mager & De Kruijff, 1995), including repression of genes involved in cell growth (e.g., ribosome biogenesis and RNA metabolism) and induction of genes canonically involved in stress defence such as ROS scavengers and HSP chaperones. Like other prokaryotic and eukaryotic microbes (Rojas et al, 2017; Sharfstein et al, 2007; Warner, 1999), diatoms halt cell division in the early stages of osmotic shock until ionic and osmotic equilibria are restored. Under such conditions, energy is probably redirected to cellular processes essential for acute stress management, rather than energetically expensive processes related to cell growth such as ribosome biogenesis (Albert et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Like other prokaryotic and eukaryotic microbes (Rojas et al, 2017;Sharfstein et al, 2007;Warner, 1999), diatoms halt cell division in the early stages of osmotic shock until ionic and osmotic equilibria are restored. Under such conditions, energy is probably redirected to cellular processes essential for acute stress management, rather than energetically expensive processes related to cell growth such as ribosome biogenesis (Albert et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These molecules are the physical basis for regulation of the neuroendocrine and immune systems in organisms. Metabolites are the final products that generated during living activities, and metabolomics analysis is study of these downstream molecules ( Sharfstein et al, 2007 ). Metabolomics is an important tool for systems biology, as it provides the ability to measure the concentrations of endogenous small molecules in biofluids and characterize the quantitative changes of the metabolites that occur in specific physiological states of organisms ( Nicholson et al, 1999 ; Sun et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%